The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3989/scimar.04340.13a
|View full text |Cite
|
Sign up to set email alerts
|

<em>Protogrammus alboranensis</em> n. sp. (Teleostei: Callionymidae), a new species of dragonet from the Alboran Sea, western Mediterranean Sea

Abstract: Summary: Protogrammus alboranensis n. sp. is described on the basis of four specimens from the Alboran Sea, western Mediterranean Sea. It is characterized within the genus Protogrammus by a total of nine unbranched rays on the second dorsal fin, eight unbranched rays on the anal fin, a very small preopercular spine with an upcurved main tip and one point on the dorsal margin, which is lacking an antrorse spine at the base, the first and second spines of the first dorsal fin filamentous and much longer than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In between, two other genera with complete ventrolateral folds of skin are distributed, Chalinops in the western Atlantic and Diplogrammus in the Indo-West Pacific. Both of the other genera live in shallow water, Chalinops at 2-27 m, Diplogrammus at 0-34 m, while Protogrammus is known from depths of 113-310 m. Reasons for this relict distribution in deeper water were discussed by Farias et al (2016). These authors suggested that the ancestors of Protogrammus have been in the area for a long time, and appeared in the region before the closure of the Tethys Sea.…”
Section: Protogrammus Alboranensis and Callionymus Reticulatusmentioning
confidence: 96%
See 4 more Smart Citations
“…In between, two other genera with complete ventrolateral folds of skin are distributed, Chalinops in the western Atlantic and Diplogrammus in the Indo-West Pacific. Both of the other genera live in shallow water, Chalinops at 2-27 m, Diplogrammus at 0-34 m, while Protogrammus is known from depths of 113-310 m. Reasons for this relict distribution in deeper water were discussed by Farias et al (2016). These authors suggested that the ancestors of Protogrammus have been in the area for a long time, and appeared in the region before the closure of the Tethys Sea.…”
Section: Protogrammus Alboranensis and Callionymus Reticulatusmentioning
confidence: 96%
“…Protogrammus alboranensis was first discovered and described by Fricke et al in Farias et al (2016: Longer than 1st D2 ray, filamentous…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations